IMPLEMENTASI METODE PEMBELAJARAN EFEKTIF PADA PIANO PRIVAT - I Gusti Ayu Gracia Wiryandhani; Fortunata Tyasrinestu (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2023)
The purpose of this study is to find out the right method in learning private piano for students who have problems in playing some songs that have not been smooth, by repetition. In piano learning, generally students (people who learn piano) use a finger drill, which is to repeat parts that have not been mastered by students. This is often used and successful in piano learning. But it was different from one student who the writer met as the subject of this research (initial E) who could not use the finger drill method. The results of the study show that hard work, strong will, and effective training must be carried out by piano students if he wants to acquire good skills and achievements in playing the piano.